Salicylic acid - Weigel, Ralf (Encyclopedia of life sciences, 2007)
Salicylic acid (SA) is an important signalling molecule in the defence response of plants against microbial pathogens. Plants are sessile and have to cope with environmental challenges without the ability to evade them actively. Responding in an appropriate manner upon pathogen attack is indispensable for their survival.